PENDAMPINGAN MAHASISWA DALAM KEGIATAN BELAJAR MENGAJAR PADA PROGRAM KAMPUS MENGAJAR - Apriyanti Widiansyah1 (Abdi Bhara, 2023)
The Teaching Campus is one of the MBKM programsthat can provide opportunities for students to innovate, becreative, and develop independence in seeking and findingknowledge during hands-on practice. The condition of literacyand numeracy that is still low in several schools requires aprogram that has been initiated by the Ministry of Education andCulture through the Teaching Campus Program. Through theTeaching Campus program it is hoped that it can providesolutions to the challenges that are being faced. The results ofthis program are to foster a sense of empathy for studentsregarding educational issues in the surrounding environment,providing opportunities for students to acquire knowledge thathas not been taught in lectures. One of them is being able to adaptin a new environment, knowing the character of each student,communicating with teachers, students and school members.Improving literacy and numeracy in placement schools, bothelementary/junior high schools, to produce quality humanresources in the education sector. Increasing technologyadaptation for students and teachers to be able to adjust totechnological developments that are developing very rapidly.